Proposed new interior design of Qasar Hadramawt Arabic Restaurant for Hadramawt (M) Sdn.Bhd at Jalan Sultan Yusuff Izzuddin 32200 Lumut, Perak / Nurul Faizatul Akma Kamarudin - Kamarudin, Nurul Faizatul Akma (Faculty of Architecture, Planning and Surveying, 2012)
The final project is about proposed new interior design of Qasar Hadramawt Arabic restaurant at Jalan Sultan Yusuff Izzuddin, Lumut, Perak for Hadramawt (M) sdn.bhd. This about a manifestation of understanding of the over all aspects of interior design for diploma level student The proposed site located at Jalan Sultan Yusuff Izzuddin, Lumut, Perak. Lumut town is a tourist centre in Perak that has been an attraction for foreign and local tourists. In addition the state is as they declared for 2012 is the Visit Perak Year. The specialty of the restaurant is theme restaurant arabic. The uniquenese about the restaurant is its has a Arabic theme with original culture style. The visitor will has instant feels like in the authentic Arabic restaurant when located in the restaurant. In specific the restaurant concept try to about the style of yemen culture. It is not surprising if the service offered is different from the restaurant available. The menu and cooking style to attract many customers to dine arid enjoy a different atmosphere than other restaurant. By here a well established visitor to come Lumut, it will boast the number of visitors.